2019
DOI: 10.1016/j.eats.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Periportal Capsulotomy: A Technique for Limited Violation of the Hip Capsule During Arthroscopy for Femoroacetabular Impingement

Abstract: Hip arthroscopy has become the standard treatment for symptomatic femoroacetabular impingement as patients have shown good outcomes and high satisfaction with this intervention. However, capsular management to gain access for intra-articular procedures remains greatly debated. Capsular closure is advocated particularly in the setting of interportal or T-capsulotomy to avoid complications of instability or nonhealing capsule. We introduce a technique for capsular management through a limited periportal capsulot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
(17 reference statements)
0
29
0
Order By: Relevance
“…Two arthroscopic portals (anterolateral and midanterior) and a periportal capsulotomy was used. 6 , 24 Based on the classification by Beck et al, 1 the acetabular cartilage, femoral cartilage, and labral condition were recorded. Procedure time from incision to closure, and traction time were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Two arthroscopic portals (anterolateral and midanterior) and a periportal capsulotomy was used. 6 , 24 Based on the classification by Beck et al, 1 the acetabular cartilage, femoral cartilage, and labral condition were recorded. Procedure time from incision to closure, and traction time were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…This senior surgeon maintains a high-volume hip arthroscopy practice and uses standard arthroscopic portals (anterolateral and midanterior) with periportal capsulotomies. 5,26 Surgical treatment for this cohort of patients included arthroscopic labral repair with osteoplasty (femoroplasty/acetabuloplasty) as indicated by type of FAI pathology. Capsular closure was performed on patients who were potentially at risk for postoperative instability or had greater joint laxity.…”
Section: Methodsmentioning
confidence: 99%
“…It is still unclear what leads to inherent or iatrogenic instability; thus, if the native head size is not substantially reduced or altered, capsular repair in the setting of a small arthroscopic capsulotomy may not be necessary in the otherwise congruent and stable hip 4,54,56 . Recently, a periportal capsulotomy technique (i.e., midanterior and anterolateral portal dilations) showed that it can preserve the iliofemoral ligament, without necessitating capsular closure 57,58 ; however, it is unclear if this applies to dysplastic hips 59 .…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%